A systematic review and meta-analysis of the impact of triclosan exposure on human semen quality - Adegbola, Cecilia Adedeji; Akhigbe, Tunmise Maryanne; Adeogun, Adetomiwa Ezekiel; Tvrdá, Eva; Pizent, Alica; Akhigbe, Roland Eghoghosoa (Frontiers in Toxicology, 2024)
IntroductionTriclosan is an antibacterial and antifungal compound that is frequently found in personal care and consumer products, and its its impact on male reproductive health is a growing concern. Despite existing experimental studies demonstrating its potential threats to male fertility, reports on its effects on human semen quality remains limited and inconsistent. Therefore, this study presents a systematic review and meta-analysis assessing the relationship between triclosan exposure and semen quality.MethodsThis study was registered with PROSPERO (CRD42024524192) and adhered to PRISMA guidelines.ResultsThe study analyzed 562 screened studies, out of which five articles including 1,312 male subjects were finally included in the study. The eligible studies were geographically diverse, with three from China, one from Belgium, and one from Poland. More so, the eligible studies were both case-control and cross-sectional. The meta-analysis revealed that triclosan exposure significantly reduced sperm concentration (Standard Mean Difference (SMD) −0.42 [95% CI: −0.75, −0.10], P = 0.01) and sperm total motility (SMD −1.30 [95% CI: −2.26, −0.34], P = 0.008). Mechanistic insights from animal and in vitro studies showed that oxidative stress may mediate the adverse effects of triclosan on semen quality.DiscussionThis meta-analysis is the first comprehensive evaluation of the impact of triclosan on human semen quality, highlighting its potential to impair male fertility through reductions in sperm concentration and motility. However, the high heterogeneity among the included studies underscores the need for further high-quality research to establish more definitive conclusions regarding the effects of triclosan exposure on human reproductive health.